1998
DOI: 10.1096/fasebj.12.15.1611
|View full text |Cite
|
Sign up to set email alerts
|

Modulating the immune response to genetic immunization

Abstract: Genetic immunization, also known as DNA or polynucleotide immunization, is a novel strategy for vaccine development in which plasmid DNA encoding either individual or a collection of antigens is directly administered to a host. Such immunization leads to host expression of the delivered foreign gene, resulting in the induction of a specific immune response against the in vivo produced antigen. DNA immunization has been shown to induce protective immune responses in several infectious disease and cancer experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 157 publications
(65 citation statements)
references
References 104 publications
1
64
0
Order By: Relevance
“…DNA-based vaccines can be prepared inexpensively and rapidly on a large scale. Furthermore, the CpG motif in plasmid DNA may cause simultaneous maturation of immature dendritic cells (DCs) and activation of mature DCs 27 and thus can preferentially induce the T helper 1 response, 28 which is important for the antitumor effect.…”
Section: Discussionmentioning
confidence: 99%
“…DNA-based vaccines can be prepared inexpensively and rapidly on a large scale. Furthermore, the CpG motif in plasmid DNA may cause simultaneous maturation of immature dendritic cells (DCs) and activation of mature DCs 27 and thus can preferentially induce the T helper 1 response, 28 which is important for the antitumor effect.…”
Section: Discussionmentioning
confidence: 99%
“…To seek an approach to increase the efficacy of the pE DNA vaccine, we tested the use of cytokines as immunological adjuvants. It has been previously demonstrated that the magnitude and nature of the immune responses to DNA vaccines can be regulated by coadministration of a broad panel of cytokine genes (25)(26)(27). Among these cytokine genes, the IL-12 gene promotes Th1 responses and cell-mediated immunity, and the IL-4 gene favors Th2 cell development and production of Abs.…”
Section: Suppression Of Immune Response and Protective Immunity To A mentioning
confidence: 99%
“…6 While peptide, protein or glycoprotein vaccines elicit mainly antibody responses, DNA vaccines allow presentation of antigen to the immune system in several ways and have the potential of inducing strong cellular responses. DNA vaccines have been shown to stimulate all three arms of the immune system, that is, antibody, helper T, and cytotoxic T-cell (CTL) responses, 16 to produce immunity in several disease models such as influenza, 17,18 HIV-1, 19,20 and hepatitis B, 21 and to protect animals from subsequent challenge. 18 The mechanisms are considered to involve antigen presentation by both myocytes and antigen-presenting cells (APCs), as well as crosspriming between the two MHC paths.…”
mentioning
confidence: 99%